6(5x-9)+9=2(x+12)+127

Simple and best practice solution for 6(5x-9)+9=2(x+12)+127 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5x-9)+9=2(x+12)+127 equation:



6(5x-9)+9=2(x+12)+127
We move all terms to the left:
6(5x-9)+9-(2(x+12)+127)=0
We multiply parentheses
30x-(2(x+12)+127)-54+9=0
We calculate terms in parentheses: -(2(x+12)+127), so:
2(x+12)+127
We multiply parentheses
2x+24+127
We add all the numbers together, and all the variables
2x+151
Back to the equation:
-(2x+151)
We add all the numbers together, and all the variables
30x-(2x+151)-45=0
We get rid of parentheses
30x-2x-151-45=0
We add all the numbers together, and all the variables
28x-196=0
We move all terms containing x to the left, all other terms to the right
28x=196
x=196/28
x=7

See similar equations:

| -q=6Q+35 | | 5+5(x+2)-2x=3x+5 | | 5y4=y+12 | | 12x-7=5x+56 | | 6+y-3=5 | | 9d-9=3-3 | | 11k=-20 | | 18-4d=5d | | 10x+12+30=15x+7 | | 18m=18+12m | | 21x+14=180,x | | 19x+28=180,x | | 25(x+10)=625 | | 2(x+3)=2(x+5)+x | | s/0.2=50 | | 6x=10=7x-2 | | 7(4-3x+12(x-5)x8)=-7(x+5)+2x | | 7-4n=51 | | 25(x+10)=525 | | -4.5p=-60.3 | | (x+60)+(x+136)=180 | | 7(43x+12(x-5)x8)=-7(x+5)+2x | | 2g-10=150 | | 5=n^2 | | (x+22)+(x+22)+(x)+(x)+(90)+(90)=180 | | 15-4k=-6k+5 | | 5x+-6=8+-2x | | x^2+11x-306=0 | | 2(y−1)+6y = −10 | | 0=-4b+2b | | 9-5(11x+7)=0 | | 6x+2=-26 |

Equations solver categories